The DIFFERENCES IN NUTRITIONAL STATUS OF INFANTS AGED 4-6 MONTHS WHO WERE EXCLUSIVELY BREASTFED AND THOSE WERE GIVEN NONEXCLUSIVE BREASTFEEDING : LITERATURE REVIEW - Frisna Dwika Maheni Maheni; Abdiana; Rafika Oktova (SEAJOM: The Southeast Asia Journal of Midwifery, 2021)
World Health Organization (WHO) recommends that babies remain given exclusive breast milk for the first six months of a baby's life. However, there were some obstacles that cause the mother to be unable to give exclusive breast milk to her baby. By the time the baby becoming 4 to 6 months, the opportunity to provided exclusive breast milk is reduced because of many factor such as working mother can be an obstacle to providing exclusive breast milk. Often for mothers prefer to provide formula milk or complementary food for their babies to make it simply.This literature review aims to determine the differences in nutritional status of infants who were exclusively breastfed and those who were not exclusively breastfed at the age of 4 to 6 months. This literature review is semi-quantitative using the narrative review method. The search for articles accessed from the PubMed, Google Scholar, and Science Direct database found 40 articles that met the criteria. There were differences in the nutritional status of infants who were exclusively breastfed and those who were given non-exclusive breastfeeding. Babies who were exclusively breastfed at the age of 4 to 6 months had a better nutritional status than babies who were given nonexclusive breastfeeding.